Three-month water degradation of resin-dentin interfaces subjected to direct and indirect exposure - Americo Correr; Atais Bacchi; Gabriel Abuna; Klissia Felizardo; Lourenço Correr-sobrinho; Mario Sinhoreti; Victor Feitosa (Cumhuriyet University, 2014)
Objectives: The aim of this study was to assess the effects direct or indirect water exposure on the 3 months hydrolytic degradation of three dentin bonding agents. Materials and methods: The samples were divided in three groups: Clearfil SE Bond, Clearfil S3, Adper Singlebond 2; and the samples were restored with Filtek Z350. Subsequent to the restorative procedures, the specimens of each group were divided into three subgroups (immersed in water deionised): Control (24h-37ºC), Direct Water exposure DWE for 3 months (37º), Indirect water exposure (IWE-3m) with enamel margins for 3 months (37ºC). After the storage the samples were sectioned into sticks and µTBS testing (EZ test) and Scanning Electronic Microscopy assessed the failure mode. The µTBS data were statistically analysed using two-way ANOVA and Tukey's test at α=0.05%. The samples were processed for nanoleakage evaluation immersed in 50 wt% ammoniacal silver nitrate (24 h), rinsed and immersed in a photo-developing solution for 8 h. Results: After 3 months CSE was the least affected by water degradation regardless the aging strategy. IWE afforded very little variation on µTBS after 3 m.  Intense nanoleakage was observed with DWE groups with increases incidence of mixed failures instead Conclusion: Bonded dentin margins are more prone to hydrolytic degradation than resin-enamel interfaces. The increased nanoleakage and the drop of bond strength showed this.